Indonesian Learners’ Self-directed Learning and Resilience in Online English Classes: Assessing Interaction with L2 Achievement - Adaninggar Septi Subekti (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
ABSTRACTThe present study was conducted to find the relationship between English for Academic Purposes (EAP) learners’ Self-directed Learning (SDL) and their achievement as measured with their EAP class grades as well as the relationship between these grades and their resilience. This study used a survey as the method of data collection and 157 learners who were enrolled in EAP online classes willingly participated in the study. Results of Pearson’s correlation and Regression analysis showed that learners’ SDL was very weakly associated with their grades (r (155) = .01, p > .05), with their SDL being unable to predict their ultimate achievement (R2 = .000). This study further found a very weak negative relationship between learners’ resilience and their grades (r (155) = -.02, p > .05). Learners’ resilience was not a predictor for their grades either (R2 = .000). As the present study is an exploratory study of the issue in question in the Indonesian context of English as a foreign language (EFL), it is suggested that further studies be conducted to establish more conclusive findings on the predictive power of learners’ SDL and resilience towards their English learning achievement. ABSTRAKStudi ini bertujuan menginvestigasi hubungan antara Self-directed Learning (SDL) pembelajar kelas Bahasa Inggris untuk tujuan akademik (EAP) dan pencapaian belajar di kelas Bahasa Inggris serta hubungan antara pencapaian belajar tersebut dengan ketahanan (resilience) mereka. Studi ini menggunakan metode survei dan sebanyak 157 pembelajar di kelas EAP bermoda daring berpartisipasi dalam studi ini. Studi ini menemukan bahwa SDL pembelajar berkorelasi sangat lemah dengan pencapaian belajar (r (155) = .01, p > .05) dan bahwa SDL tidak mampu memprediksi pencapaian belajar (R2 = .000). Studi ini juga menemukan bahwa ketahanan pembelajar berkorelasi sangat lemah dengan pencapaian belajar (r (155) = -.02, p > .05) dan tidak mampu memprediksi pencapaian belajar (R2 = .000). Karena studi ini termasuk studi awal dalam kajian SDL dan ketahanan pembelajar dalam kaitannya dengan pencapaian belajar pada konteks pembelajaran Bahasa Inggris sebagai bahasa asing di Indonesia, terkait dengan hasil studi ini, disarankan dilakukan studi-studi lain dalam konteks Indonesia. Studi-studi ini dapat dilakukan untuk mendapatkan kesimpulan yang lebih solid terkait besar kecilnya kemampuan SDL dan ketahanan pembelajar dalam memprediksi pencapaian belajar mereka dalam Bahasa Inggris.